Architecture and asceticism cultural interaction between Syria and Georgia in late antiquity - Loosley, Emma (Boston Brill, 2018)
In Architecture and Asceticism Loosley Leeming presents the first interdisciplinary exploration of Late Antique Syrian-Georgian relations available in English. The author takes an inter-disciplinary approach and examines the question from archaeological, art historical, historical, literary and theological viewpoints to try and explore the relationship as thoroughly as possible. Taking the Georgian belief that 'Thirteen Syrian Fathers' introduced monasticism to the country in the sixth century as a starting point, this volume explores the evidence for trade, cultural and religious relations between Syria and the Kingdom of Kartli (what is now eastern Georgia) between the fourth and seventh centuries CE. It considers whether there is any evidence to support the medieval texts and tries to place this posited relationship within a wider regional context
Includes bibliographical references and index
Keywords: Orthodox Eastern Church -- Georgia (Republic) -- History; Syriac Christians -- Georgia (Republic); Church History; Church Architecture -- Syria; Church Architecture -- Georgia (Republic); HISTORY ; Middle East ; General; HISTORY / Middle East / General; Syriac Christians; Syria; Georgia (Republic); History; Orthodox Eastern Church; Church Architecture; Church History; Church History; Chrétiens syriaques - Géorgie (République); Architecture chrétienne - Syrie; Église - Histoire; Architecture chrétienne - Géorgie (République)